Re-Locating Religion in the Digital Age - Preda, Alina (Journal for the study of religions and ideologies, 2024)
Due to the fact that formal systems of religious thought have developed, throughout the ages, in response to the pressures of informal daily practices that the countless believers worldwide have tended to adopt, religion and technology have always been intertwined in a complex web of relationships. The aim of this article is to provide an insight into the nexus between religion and technology, to trace their intricate entanglement, and to identify the threats faced by religion in the Digital Age. Although the Internet facilitates the reinforcement of believers’ religious identity and the formation of transnational religious communities, recent research on the wide cultural effects of Internet-use, robotics, and AI points to a notable decline in religiosity brought forth by this automated environment. As automation is increasingly diminishing the utilitarian significance of religion in various global regions, philosophical counselling can fill the spiritual void left in the lives of non-believers by helping them face existential quandaries that do not require the involvement of psychotherapists. Given the chequered history marking the relationship between religion and technology, it is indisputable that, as technology advances, religious institutions and practitioners, as well as individuals who renounce religious affiliation, will continue to grapple with both the difficulties and the opportunities it brings.